Pengaruh Penggunaan QRIS dalam meningkatkan efektifitas dan efiisiensi UMKM di kota Ambon - Hasmawati, Hasmawati; Siahaya, Septina Louisa; Aponno, Chrestiana (Journal of Applied Accounting, 2025)
This study aims to understand the real role of QRIS in increasing the effectiveness and efficiency of MSMEs, as well as providing input for policy makers and business actors in encouraging the digitalization of the MSME sector more widely and evenly in the city of Ambon. QRIS as a standardized digital payment system in Indonesia is expected to provide convenience in transactions, speed up the payment process and reduce the use of cash. The method used in this study is descriptive qualitative with a literature method through a literature study sourced from journals of previous research results related to the title and through access to several data obtained from the website as information publications. The results of the study show that the Use of the QRIS Payment System has a positive effect on increasing the income of MSMEs in Ambon City. However, there are several obstacles that are felt, namely: There are still those who do not understand how to use QRIS and are constrained by internet access in several areas of Maluku. So it is hoped that the government and related parties can take part in optimizing the benefits of QRIS in accelerating economic growth. Keywords: QRIS, Effectiveness, Efficiency, MSMEs